2013
DOI: 10.1371/journal.pone.0069502
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Arginine and Glutamine on Alleviating the Impairment Induced by Deoxynivalenol Stress and Immune Relevant Cytokines in Growing Pigs

Abstract: Deoxynivalenol (DON) is a mycotoxin that reduces feed intake and animal performance, especially in swine. Arginine and glutamine play important roles in swine nutrition. The objective of this study was to determine the effects of dietary supplementation with arginine and glutamine on both the impairment induced by DON stress and immune relevant cytokines in growing pigs. A total of forty 60-d-old healthy growing pigs with a mean body weight of 16.28±1.54 kg were randomly divided into 5 groups, and assigned to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
57
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 57 publications
(59 reference statements)
12
57
2
Order By: Relevance
“…Meanwhile, DON slightly increased serum TP and ALB concentrations compared with the control. These outcomes are similar to previous studies, which provided evidence that liver injury was induced by AFB1, ZEA and DON (Bagherzadeh Kasmani et al, 2012;Jiang et al, 2011;Wu et al, 2013a). Notably, the combination of mycotoxins AFB1 + DON displaying a synergetic effect on ALT, and AFB1 + ZEA displaying antagonistic effect on AST in vivo are newly illustrated by us in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Meanwhile, DON slightly increased serum TP and ALB concentrations compared with the control. These outcomes are similar to previous studies, which provided evidence that liver injury was induced by AFB1, ZEA and DON (Bagherzadeh Kasmani et al, 2012;Jiang et al, 2011;Wu et al, 2013a). Notably, the combination of mycotoxins AFB1 + DON displaying a synergetic effect on ALT, and AFB1 + ZEA displaying antagonistic effect on AST in vivo are newly illustrated by us in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The activities of enzymes such as ALT and AST as well as the concentrations of TP and ALB in serum have been described as valuable indicators of hepatic injury and function (Bagherzadeh Kasmani et al, 2012;Jiang et al, 2011;Wu et al, 2013a). In this study, administration of AFB1, ZEA and DON increased ALT and/or AST activity in serum.…”
Section: Discussionmentioning
confidence: 53%
“…This result suggests a reduction in oxidative stress in response to glutamine supplementation. Similarly, numerous well-designed investigations have consistently indicated that glutamine increases anti-oxidative capacity in mice (Ren et al 2014b;Cruzat et al 2014), rats (Xu et al 2014), pigs (Wu et al 2011b(Wu et al , 2013cWang et al 2008), and sheep (Sawant et al 2014;Washburn et al 2013). Furthermore, we found that dietary supplementation with 0.5 % glutamine decreased the expression of virulence factors of P. multocida, as we previously reported (Ren et al 2013e).…”
Section: Discussionsupporting
confidence: 85%
“…This is surprising because glutamine has been reported to enhance general immune responses in animals, including pigs (Wu et al 2013c), mice (Ren et al 2013a), and cows (Caroprese et al ). Of note, mRNA levels for GPx-1 and CuZnSOD were lower in the spleen of glutamine-supplemented mice, compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of GLU, LDL-C, TG, CHO, and HDL-C were tested as a reflection of the metabolism and inner organ status of the animal (Wu et al, 2013). The present study revealed that supplementations with TP and LB influence serum LDL-C, TG, and HDL-C concentrations in chickens.…”
Section: Discussionmentioning
confidence: 65%